Rangeland degradation in the steppe zone of Mongolia (Mongolian Journal of Agricultural Sciences, 2023)
Changes in rangeland management practices and global warming are to blame for the degradation of Mongolia's rangelands. Rangelands might deteriorate as a result of the expected repercussions from grazing disturbances, which is likely to make the situation worse [1] The people of Mongolia are aware of the growing degradation of rangelands, that is linked to the confluence of unsustainable behaviors and drought events. On the other hand, little research has been done on how naturally degraded rangelands recover and if restoration is necessary. In order to evaluate the state of rangelands and determine the effects of management methods across Mongolia, this article explores the application of "recovery class" principles in rangeland management. In order to test the recovery in steppe zone, the 25x25 size fence was set up. Outside of the fence was grazed continuously for year-round and comparative study of vegetation in outside and inside was carried. Because of unproper grazing, the productivity and species diversity declines. Also, decline in total and species cover declined. Du to conservative grazing and resting inside of fence, vegetation had a great recovery.